Exercise and Dietary-Protein as a Countermeasure to Skeletal Muscle Weakness: Liverpool Hope University – Sarcopenia Aging Trial (LHU-SAT) - Kirk, Ben; Mooney, Kate; Amirabdollahian, Farzad; Khaiyat, Omid (Frontiers in Physiology, 2019)
See manuscript submission